Enhanced Copper Tolerance in Silene vulgaris (Moench) Garcke Populations from Copper Mines Is Associated with Increased Transcript Levels of a 2b-Type Metallothionein Gene - van Hoof, Nathalie A.L.M. (American Society of Plant Physiologists, 2001)
Silene vulgaris (Moench) Garcke has evolved populations with extremely high levels of copper tolerance. To evaluate the role of metallothioneins (MTs) in copper tolerance in S. vulgaris, we screened a cDNA library derived from a highly copper-tolerant population using Arabidopsis-based MT probes and identified an MT2b-like gene. When expressed in yeast, this gene, SvMT2b, restored cadmium and copper tolerance in different hypersensitive strains. Northern-blot analysis and quantitative reverse transcriptase-PCR showed that plants from the copper-tolerant S. vulgaris populations had significantly higher transcript levels of SvMT2b than plants from the copper-sensitive populations, both in roots and shoots and with and without copper exposure. Southern-blot analysis suggested that the higher expression of the latter allele was caused by gene amplification. Segregating families of crosses between copper-sensitive and copper-tolerant plants exhibited a 1 to 3 segregation for SvMT2b expression. Allele-specific PCR showed that low-expression F(3) plants were homozygous for the allele inherited from the copper-sensitive parent, whereas high-expression plants possessed at least one allele from the tolerant parent. SvMT2b expression did not cosegregate with copper tolerance in crosses between sensitive and tolerant plants. However, a significant cosegregation with copper tolerance did occur in families derived from crosses between moderately tolerant F(3) plants with different SvMT2b genotypes. Thus, overexpression of SvMT2b conferred copper tolerance although only within the genetic background of a copper tolerant plant.